POTENSI BAKTERI KITINOLITIK SUMBER AIR PANAS SEBAGAI PENGENDALI HAYATI LARVA Aedes aegypti L. - Fitria Ardani; Yekki Yasmin; Lenni Fitri (Universitas Syiah Kuala, 2012)
The purpose of this study was to discover the potential of isolate chitinolitic bacteria, hot springs, as biological control of Aedes aegypti L. larva. This research used Completed Randomized Designed (RAL) factorial with two factor, isolate types and concentration of isolatechitinolitic bacteria. The research procedure includes the maintenances of Aedes aegypti L. larva, isolation and selection of chitinolitic bacteria, and biological test. Data were processed by using Varian Analysis (ANAVA). The result of this study indicated that four isolates were test on larva of Aedes aegypti L. masquito, instar II. Giving different isolat chitinolitic bacteria and concentration showed no significant differences in larva death (P0,05). The highest average of larva death was exhibited at the treatments of 1% of IS 2 and IS 3 isolate. The occurance of chitinolitic bacteria influenced the growth of pupa, it can be showed that the pupa was not formed from each consentration and isolate that caused the death in larva signed by the part of body and larva siphon were pale and digestive tract was dark.